2018
DOI: 10.1200/jco.2018.36.15_suppl.6080
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of surgical site infection after oral cancer surgery by topical tetracycline: Results of a multicenter randomized control trial.

Abstract: Background: In a pilot study, we showed that topical administration of a tetracycline could decrease oral bacteria levels for 6 hours in patients who underwent oral cancer surgery combined with tracheotomy and flap reconstruction. This multicenter, randomized control trial aimed to investigate the effectiveness of topical application of tetracycline ointment for prevention of surgical site infection (SSI) associated with major oral cancer surgery.Methods: One hundred seventeen patients who underwent oral cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(37 reference statements)
0
5
1
Order By: Relevance
“…Many species of indigenous bacteria are present in the oral cavity 7) , and exposing the neck surgical field to them is a risk factor for postoperative infection. Earlier studies have reported the incidence of SSIs to be 21.3% and 36.1%, showing no significant difference to that observed in the present study 3,8) .…”
Section: Discussioncontrasting
confidence: 90%
“…Many species of indigenous bacteria are present in the oral cavity 7) , and exposing the neck surgical field to them is a risk factor for postoperative infection. Earlier studies have reported the incidence of SSIs to be 21.3% and 36.1%, showing no significant difference to that observed in the present study 3,8) .…”
Section: Discussioncontrasting
confidence: 90%
“…Hayashida et al [14] reported that irrigation with tap water reduces oral bacteria in ventilated patients, but the number of bacteria in oropharyngeal fluid increased within 3 h after irrigation. Funahara et al described that topical tetracycline ointment on the tongue reduces the number of bacteria in oropharyngeal fluid for about 6 h [16]; furthermore, in a multicenter randomized clinical trial, topical application of tetracycline ointment on the tongue every 6 h for 24 h after surgery significantly prevented surgical site infection in patients undergoing oral cancer surgery with flap reconstruction and tracheotomy [17]. Some studies have investigated the effects of oral decontamination on VAP prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies investigated risk factors of SSI by examining variable sets of factors for their potential association with infection; however, some those factors lacked reproducibility. Risk factors previously reported in literature include the following: the presence of comorbidities, 25,27 tobacco use, 8 prior radiotherapy, 9,20 prior chemotherapy, 23 type of surgery, 23,25 clean-contaminated procedures, 9,20 not using prophylactic antibiotic for cleancontaminated procedures, 28,29 longer surgery, 22,27,30 flap reconstruction, 8 neck dissection, 31,32 tracheotomy, 9,18,31 high American Society of Anesthesiologists score, 22 blood loss, 23,27 presence of lymph node metastasis, 8,25 management of a recurrent disease, 18,21 oral cavity cancer as opposed to other head and neck cancers, 9 the inflammatory state of the ear at the time of surgery, 33 preoperative high liver function tests, 6 preoperative low sodium levels, 6 and early postoperative hypoalbuminemia. 34 The study also examined risk factors of readmission with SSI and identified the following independent predictors: 1 comorbidities, history of chemotherapy, cancer diagnosis, site and class of surgery, and neck dissection.…”
Section: Discussionmentioning
confidence: 99%